Perspective of nurses on effective factors on their decisions to administer PRN analgesics to children after surgery - Karimi; R. Parsa-Yekta; Z. Mehran; A. Nik-Farid; L. (Tehran University of Medical Sciences, 2002)
Post-surgery pain is usually controlled by PRN drugs administered by nurses. According to the decision-making theories, this clinical decision-making depends on three factors: nurse-related factors; child-related factors; and hospital-related factors. This study deals with the first and second factors mentioned. This descriptive-analytic study aims at determining the perspective of nurses on factors which affect their decisions to administer the analgesic PRN to children after surgery in several chosen hospitals of Tehran. The study used a standardized questionnaire to collect data from 57 nurses in pediatric surgery wards. The questionnaire consisted of three parts: 1) nurses demographic data 2) 20 clinical scenario for nurses to make a decision for prescribing either analgesic medication, non-analgesic medication or no medication where necessary and 3) 12 factors which affect clinical decision-making in using analgesics.(in prioritizing among the above mentioned). The results show that factors such as age, nursing experience, pediatric nursing experience and motherhood were significantly related to choosing to use analgesics. Education and personal experience of extreme pain was also related to the type of analgesic chosen. Concerning the specifics of the children there was a significant difference between the choice to use analgesics and the type of analgesic used according to the various ages of the children. There was also a significant relationship between the type of surgery and the time of surgery and with the choice to use analgesics and the type of analgesics used, such that medication and analgesics were administered more frequently for complicated surgeries and in first 24 hours after surgery. Type of surgery, severity of pain, time of surgery and uneasy behaviors were selected respectively as the most effective in the administration of PRN analgesic drugs. Nurse and child related factors strongly influence nurses in making decisions to administer PRN analgesics postoperatively.